PERAN GURU DALAM MENANAMKAN KEPEDULIAN SISWA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM - Irawan, Lestari; Munirah, Munirah; Datunsolang, Rinaldi (DIRASATUL IBTIDAIYAH, 2024)
AbstractIslamic History and Culture Education is one of the subjects taught at Madrasah Ibtidaiyah Muhammadiyah Gorontalo North City Branch. However, many students do not understand the importance of Islamic history and culture, and tend to find this lesson boring. Therefore, it is important to develop effective and interesting learning methods for students to increase their interest and understanding of Islamic history and culture. The type of research used is qualitative. Qualitative research is research used to examine the natural conditions of objects (as opposed to experiments). Instilling students' awareness of the subject of Islamic cultural history requires an active and strategic role from the teacher. At MI Muhammadiyah North City, teachers have several important roles which are implemented through various approaches and methods to achieve this goal. Apart from that, they must also be able to integrate cultural and religious values in teaching, so that students can understand the relevance of history in everyday life. "As a teacher, I understand that success in instilling historical and cultural awareness and values in students is greatly influenced by several key factors. "These factors are usually influenced by relevant and interesting teaching methods, contextual use of media, and the teacher's ability to be a good role model." The role of the teacher is very important, especially in the learning context which aims to instill certain values in students.Keywords: Instilling student awareness in Islamic cultural history lessons. AbstrakPendidikan Sejarah dan Kebudayaan Islam adalah salah satu mata pelajaran yang diajarkan di Madrasah Ibtidaiyah Muhammadiyah Gorontalo Cabang Kota Utara. Namun, banyak siswa yang kurang memahami pentingnya sejarah dan budaya Islam, dan cenderung menganggap pelajaran ini membosankan. Oleh karena itu, penting untuk mengembangkan metode pembelajaran yang efektif dan menarik bagi siswa untuk meningkatkan minat dan pemahaman mereka terhadap sejarah dan budaya Islam. Jenis penelitian yang di gunakann yaitu kualitatif. Penelitian kualitatif adalah penelitian yang digunakan untuk meneliti pada kondisi objek yang alamiah (sebagai lawannya eksperimen). Menanamkan kepedulian siswa terhadap mata pelajaran sejarah kebudayaan Islammmemerlukan peran aktif dan strategis dari guru. Di MI Muhammadiyah kota Utara, guru memiliki beberapa peran penting yang diimplementasikan melalui berbagai pendekatan dan metode untuk mencapai tujuan ini. Selain itu, mereka juga harus mampu mengintegrasikan nilai-nilai budaya dan agama dalam pengajaran, sehingga siswa dapat memahami relevansi sejarah dalam kehidupan sehari-hari. “sebagai seorang guru saya memahami bahwa keberhasilan dalam menanamkan kepedulian dan nilai-nilai sejarah serta budaya kepada siswa sangat dipengaruhi oleh beberapa faktor kunci. Faktor tersebut biasanya dipengaruhi oleh metode pengajaran yang relevan dan menarik, penggunaan media yang kontekstual, serta kemampuan guru untuk menjadi teladan yang baik.” peran guru sangatlah penting, terutama dalam konteks pembelajaran yang bertujuan untuk menanamkan nilai-nilai tertentu pada siswa. Kata Kunci: Menanamkan kepedulian siswa pada pelajaran sejarah kebudayaan islam